Musicoterapia como campo do representacional: educadores sociais e a produção de corpos sonoros e subjetividades - VALENTIN, Fernanda (2010)
When taking knowledge of the existence of institutions of internment for adolescent authors of infracionais acts, appeared the interest in knowing them and investigating the reality of the social educators who act there. In a generalized manner, it is noticed that these professionals are citizens diverse anxiogenic situations e, on the other hand, is not given the had attention to the personal dimension of the same ones. Ahead of this, one perceived that the potential of the Music Therapy could contribute in the social education context, since this therapeutical one privileges the interaction between body, sound and music. Thus, the present study it had as objective generality to investigate as the Music Therapy can contribute in the production of sonorous bodies and subjectivities of social educators who act in centers of internment and attendance for adolescent authors of infracionais acts, aiming at to identify the music therapeutics experiences as field of the representational. One is about a qualitative research, with characteristic to interdisciplinary, having as referential theoretician workmanships of the areas of Social Education, Social Psychology, Cultural History, Music, Music Therapy and, still, the Theories of the Social Representations evidenced mainly in the thoughts of Moscovici and Chartier. The field research was carried through next to two groups formed for social educators of two units of internment, both located in the city of Goiânia. It was possible, to the end of the research, to verify that the participant educators had tried a rescue of its proper sounds, the creation of new noises and subjectivities, and a corporeity connected to different the sensible ones and the proper life. When taking knowledge of the existence of institutions of internment for adolescent authors of infracionais acts, appeared the interest in knowing them and investigating the reality of the social educators who act there. In a generalized manner, it is noticed that these professionals are citizens diverse anxiogenic situations e, on the other hand, is not given the had attention to the personal dimension of the same ones. Ahead of this, one perceived that the potential of the Music Therapy could contribute in the social education context, since this therapeutical one privileges the interaction between body, sound and music. Thus, the present study it had as objective generality to investigate as the Music Therapy can contribute in the production of sonorous bodies and subjectivities of social educators who act in centers of internment and attendance for adolescent authors of infracionais acts, aiming at to identify the music therapeutics experiences as field of the representational. One is about a qualitative research, with characteristic to interdisciplinary, having as referential theoretician workmanships of the areas of Social Education, Social Psychology, Cultural History, Music, Music Therapy and, still, the Theories of the Social Representations evidenced mainly in the thoughts of Moscovici and Chartier. The field research was carried through next to two groups formed for social educators of two units of internment, both located in the city of Goiânia. It was possible, to the end of the research, to verify that the participant educators had tried a rescue of its proper sounds, the creation of new noises and subjectivities, and a corporeity connected to different the sensible ones and the proper life.